The aboriginal population of the Far East in the Russian-Japanese trade in the 18th – 19th centuries (based on pre-revolutionary sources) - Shkunov V.N. (Японские исследования)
The article is devoted to the definition of the role and importance of the participation of the indigenous peoples of the Far East in the formation and development of Russian-Japanese trade during the 18th – 19th centuries. The traditional crafts of the aborigines of the Far Eastern Territory were of undoubted interest to Russian entrepreneurs who sought to expand trade relations with neighboring Japan. Before the conclusion of the Treaty of Shimoda in 1855, Russian merchants in need of certain goods resorted to the intermediary services of the Ainu, who exchanged Japanese goods for Russian ones. The article provides concrete facts about the indirect participation of the aborigines of the Far East in Russian-Japanese trade, information about goods, prices, supply channels, etc. It notes the changes in the life of the aboriginal population under the influence of barter trade, their transition to settled life, borrowing of traditions of everyday life from Russians, and their reorientation to new occupations, influenced by the needs of foreign trade. In particular, it discusses the specific features of traditional occupations of the aborigines of the Far East: the Taz, the Negidals, the Oroks, the Nivkh, the Gilyaks, the Tungus, the Goldi, the Orochen, etc., as well as ways of their involvement in barter trade and realization of products of traditional crafts in the Japanese market. The article specifically focuses on the participation of the Ainu subjects of Japan and the Russian Empire in Russian-Japanese trade, notes the peculiarities of the attitude of Russian and Japanese authorities to the Ainu, their interaction with Russian entrepreneurs. It also notes the participation of Koreans and the Chinese residing in the Russian Far East in Russian-Japanese trade. The article emphasizes the importance of Russian entrepreneurs’ selling furs, fish, seafoods, seaweed, ginseng, marine mammals products obtained through barter trade from the Far Eastern aborigines in the Japanese market. It analyzes the bilateral international trade treaties between the Russian Empire and Japan in the studied period. The article uses rare pre-revolutionary archival documents, as well as sources in Russian, English, French, Spanish, and German.